Konstruksi Gender Dalam Tafsir Marah Labid Karya Imam Nawawi Al-Bantani - Rafi, Muhammad (PSGA LP2M IAIN Pontianak, 2023)
This article discusses gender construction in the Marah Labid by Sheikh Nawawi al-Bantani al-Jawi. In addition, it also discusses how the correlation between culture and society in which Nawawi al-Bantani lives with the product of interpretation is produced, so that it can be seen clearly the logical reasons and historical influences of Nawawi in interpreting the Qur'an. Then at the end, the interpretation of gender bias - if any - that can lead to injustice and discrimination will be eliminated. This study is interesting to do, because no one has examined gender construction in this book which is actually produced by the Indonesian Scholar and used as one of the sources of learning of Islamic teachings in Indonesia.